2020
DOI: 10.5847/wjem.j.1920-8642.2020.01.005
|View full text |Cite
|
Sign up to set email alerts
|

The first two cases of transcatheter mitral valve repair with ARTO system in Asia

Abstract: BACKGROUND: MAVERIC (Mitral Valve Repair Clinical Trial) validates the safety and effi cacy of the ARTO system. We here report the fi rst two successful cases of utilizing the ARTO system in patients with symptomatic heart failure (HF) with functional mitral regurgitation (FMR) in Asia. METHODS: Two patients, aged 70 and 63, had severe HF with FMR. Transesophageal echocardiography confirmed that the left ventricular ejection fractions were less than 50% with severe mitral regurgitation (MR) in both patients. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
(14 reference statements)
1
2
0
Order By: Relevance
“…Both guideline-directed medicine therapy (GDMT) and transcatheter mitral valve repair have been shown to slow the progression of MR. A randomized trial of transcatheter mitral valve repair showed that 10.61% of HF patients in the control group receiving recommended medication therapy for one year had a recovered MR in the prospective study; by contrast, the device group had a higher proportion (37.42%) [ 22 ]. Similar results were observed in Chinese patients [ 21 ]. We then examined the characteristics and risk factors for MR in greater detail.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Both guideline-directed medicine therapy (GDMT) and transcatheter mitral valve repair have been shown to slow the progression of MR. A randomized trial of transcatheter mitral valve repair showed that 10.61% of HF patients in the control group receiving recommended medication therapy for one year had a recovered MR in the prospective study; by contrast, the device group had a higher proportion (37.42%) [ 22 ]. Similar results were observed in Chinese patients [ 21 ]. We then examined the characteristics and risk factors for MR in greater detail.…”
Section: Discussionsupporting
confidence: 89%
“…To begin, a significant proportion of HF patients in our study had MR, particularly the HFrEF patients. Due to the high prevalence of HF in China, a significant proportion of MR patients have a poor prognosis and may benefit from mitral valve repair, as clinical trials continue [ 20 , 21 ]. Second, MR is associated with deteriorated cardiac function, including atrial and ventricle abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…[15,16] The new PPMI rate in this study was lower (9.6%), which was also lower than in the Chinese Venus A analysis (18.8%). [17] In this study, the 18-mm balloon during BAV was used in 60.6% of patients. This indicates that the balloon size during BAV in our cohort was generally smaller than that in other studies.…”
Section: Discussionmentioning
confidence: 99%